Theoretical and Experimental Investigation on Dynamic Response of Asphalt Pavement Under Vibration Compaction - Shan, Hong-Yu; Dan, Han-Cheng; Wang, Shi-Ping; Liu, Xiang; Wang, Hao (Frontiers in Materials, 2022)
This study aims to investigate the dynamic response regulation by combining the theoretical analysis and field test under the vibration rolling condition. Based on the viscoelastic theory of a multilayer system, the dynamic stiffness method (DSM) incorporating multidimensional Fourier transform is proposed to solve the 3-dimensional (3D) dynamic response of pavement under vibration compaction. The stiffness matrix of each pavement layer and the global stiffness matrix of the whole pavement structure are obtained. By combining vibration load with boundary conditions, the 3D exact solution is obtained and validated by the finite element method. In addition, the field test is also conducted using a series of sensors and equipment (e.g., SmartRock sensor, acceleration sensor, temperature sensors, and non-nuclear density meter) to calibrate the theoretical model to determine the wave number and dynamic modulus during the vibration rolling process. Then, considering the factors during compaction, the rules of displacement variation and pavement acceleration are investigated in terms of modulus, thickness, and density. The results show that the 3D displacement and acceleration components both vibrate with high frequencies during compaction, and peak acceleration in the vertical direction prevails. For the vertical displacement, its distribution beneath the drum of the roller is almost even except that it drops to zero abruptly around the drum edge. The relationship between thickness and acceleration follows a linear function, and the acceleration on the pavement surface rises when the thickness increases. Although the density and modulus increase with rolling times, the effect of modulus on acceleration is more obvious and prominent than that of density. In summary, the DSM presented in this article provides a robust method to calculate the dynamic response of pavement under vibratory compaction and to back-calculate the modulus of compacted pavement layers. Moreover, the regulation also sheds insight on the understanding of vibration compaction mechanism that there is a potentially strong correlation between compaction state, modulus, and vibration acceleration.